(untitled) (Comprehensive Journal of Science, 2026)
This study was conducted randomly on 100 pregnant women attending the AL Ain Diabetes and Endocrinology Center in Sorman, from August 2024 to October 2024, to determine the incidence of urinary tract infictions among pregnant women. The study concluded that 26% of cases did not suffer from urinary tract infections and 74% Among the cases suffering from urinary tract inficions, the highest age group in which infection occurred was the group from (25 to 35years) at arate of 50%, and the most vulnerable month of pregnancy to urinary tract infections was the third mkoth at rate of 21.5% the lowest cases were in the ninth month at 1%, and pregnant women were more likely to develop a urinary tract infection during pregnancy than those who had one or three previous births at rate of 23% the percentage of cases that had previously suffered from a urinary tract infection was 62.16%, and those who had not previously suffered from a urinary tract infection was (37.84%) women who had three previous births had the highest percentages (21.7%) Among pregnant women who are currently suffering from a urinary tract infection during pregnancy and they previously suffered from a urinary tract infection, and on the other hand, women who had one previous birth (28.60%) were among the pregnant women who suffered the most urinary tract infections during pregnancy currently, and had not suffered from any urinary tract infection previously.